Strategi SEO Berbasis WEB untuk Pengoptimalan Pemasaran UMKM Berbasis Digital: Memanfaatkan Peluang Ekonomi Digital - Okprana, Harly; Darma, Surya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to optimize digital marketing for Micro, Small, and Medium Enterprises (MSMEs) by applying web-based SEO (Search Engine Optimization) methods to capitalize on digital economic opportunities. The main issue faced by MSMEs is low visibility on search engines, which impacts organic traffic and online market competitiveness. The proposed solution is an SEO strategy that includes content optimization, website structure, relevant keywords, quality backlinks, and search engine algorithm analysis. The system used involves a case study at Primecom Store in Pematangsiantar, North Sumatra, with the implementation of SEO steps such as on-page and off-page optimization, and monitoring using Google Analytics. Over six months of implementation, the research results show an increase in organic traffic from 200 to 523 visits per month, an average keyword ranking improvement of 35%, and page visits rising from 100 to 417 per month. Additionally, quality backlinks increased from 10 to 40, while page load time decreased from 4.5 seconds to 2.8 seconds. These results demonstrate that the implementation of a web-based SEO strategy can enhance MSMEs' visibility and competitiveness in the digital market. This research provides practical recommendations for MSMEs to effectively leverage digital economic opportunities through an integrated SEO strategy.